The transcription factor PagLBD3 contributes to the regulation of secondary growth in Populus. (27th July 2021) - Han, Zhen; Yang, Tong; Guo, Ying; Cui, Wen-Hui; Yao, Li-Juan; Li, Gang; Wu, Ai-Min; Li, Ji-Hong; Liu, Li-Jun
Abstract: LATERAL ORGAN BOUNDARIES DOMAIN ( LBD ) genes encode plant-specific transcription factors that participate in regulating various developmental processes. In this study, we genetically characterized PagLBD3 encoding an important regulator of secondary growth in poplar ( Populus alba × Populus glandulosa ). Overexpression of PagLBD3 increased stem secondary growth in Populus with a significantly higher rate of cambial cell differentiation into phloem, while dominant repression of PagLBD3 significantly decreased the rate of cambial cell differentiation into phloem. Furthermore, we identified 1756 PagLBD3 genome-wide putative direct target genes (DTGs) through RNA sequencing (RNA-seq)-coupled DNA affinity purification followed by sequencing (DAP-seq) assays. Gene Ontology analysis revealed that genes regulated by PagLBD3 were enriched in biological pathways regulating meristem development, xylem development, and auxin transport. Several central regulator genes for vascular development, including PHLOEM INTERCALATED WITH XYLEM ( PXY ), WUSCHEL RELATED HOMEOBOX4 ( WOX4 ), Secondary Wall-Associated NAC Domain 1s ( SND1-B2 ), and Vascular-Related NAC-Domain 6s ( VND6-B1 ), were identified as PagLBD3 DTGs. Together, our results indicate that PagLBD3 and its DTGs form a complex transcriptional network to modulate cambium activity and phloem/xylem differentiation. Abstract : The transcription factor PagLBD3 is an important regulator of secondary growth in Populus in a complex transcriptional network coordinating the balance of cambium cell division and phloem/xylem differentiation.